2015
DOI: 10.18805/lr.v0iof.6780
|View full text |Cite
|
Sign up to set email alerts
|

Co-inoculation of Mesorhizobium sp. and plant growth promoting rhizobacteria Pseudomonas sp. as bio-enhancer and bio-fertilizer in chickpea (Cicer arietinum L.)

Abstract: The present investigation was undertaken to study the synergistic effect of recommended Mesorhizobium sp. (LGR -33) (Meso) and native potential PGPR Pseudomonas sp. (PGPR 2 and PGPR 3) along with reference strain Pseudomonas diminuta (LK884) on bio-enhancing activity, symbiotic parameters and grain yield in desi (PBG 1) and kabuli (BG 1053) under field conditions in chickpea during rabi 2009-2010. Significant improvement in growth and symbiotic parameters was observed with co-inoculation of Mesorhizobium sp. w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…These findings are in line with those of Yagmur and Kaydan (2011) and Tagore et al (2014) in chickpea. Further, Kaur et al (2015) reported 61.1% and 11.4% greater grain N and P content, respectively in Mesorhizobium inoculated chickpea. Kumar et al (2014) also found significantly higher protein content in Rhizobium inoculated plots in comparison to uninoculated control.…”
Section: Symbiotic Parametersmentioning
confidence: 83%
“…These findings are in line with those of Yagmur and Kaydan (2011) and Tagore et al (2014) in chickpea. Further, Kaur et al (2015) reported 61.1% and 11.4% greater grain N and P content, respectively in Mesorhizobium inoculated chickpea. Kumar et al (2014) also found significantly higher protein content in Rhizobium inoculated plots in comparison to uninoculated control.…”
Section: Symbiotic Parametersmentioning
confidence: 83%
“…Legumes show improved nodulation and grain yield when co-inoculated with PGP bacteria compared to inoculation with rhizobia alone (Rokhzadi et al, 2008;Yang et al, 2009). Co-inoculation of legumes, chickpea in particular, with rhizobia and PGPR are reported to enhance nodulation and nitrogen fixation (Sindhu and Dadarwal, 2001;Garcia et al, 2004;Valverde et al, 2006;Kaur et al, 2015). Hence, the synergistic benefits of these three diazotrophic bacteria could be exploited for improving grain yield in chickpea through better nodulation and N 2 fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Effect of biological fertilizers on leaf may depend et al,2017). Kaur et al,(2015) in a study on chickpea stated that Rhizobium inoculation significantly increased chlorophyll content as compared to control.…”
Section: Physiological Characteristics Chlorophyll Content Indexmentioning
confidence: 98%